Rational and Adaptive Expectations in the Present Value Model of Hyperinflation - Beladi, Hamid; Choudhary, Munit A. S.; Parai, Amar K. (The Review of Economics and Statistics, 1993)
Hamid Beladi, Munit A. S. Choudhary, Amar K. Parai, Rational and Adaptive Expectations in the Present Value Model of Hyperinflation, The Review of Economics and Statistics, Vol. 75, No. 3 (Aug., 1993), pp. 511-514